2008
DOI: 10.1007/s12306-008-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical bilateral traumatic fracture dislocation of the hip: A report of two cases

Abstract: We report on two cases of simultaneous asymmetrical bilateral hip dislocation. Both patients were involved in car accidents. The first case is a 23-year-old man who had a bilateral hip dislocation, anterior on the right side and posterior on the left associated with bilateral femoral head fracture. The second case presented the same dislocations of the hips associated with acetabular fracture on the right side. Closed reduction of the hips was performed in both cases. In the first case the femoral head fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…[1] In the English literature, there have been a total of 58 cases with bilateral hip dislocation. [2,3] Those are cases with pure dislocation or with accompanying injuries like sciatic nerve injury, femoral fracture, patellar fracture, and acetabulum and femoral head fracture. [11,12] Only four cases with asymmetric hip dislocation and unilateral acetabular fracture have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] In the English literature, there have been a total of 58 cases with bilateral hip dislocation. [2,3] Those are cases with pure dislocation or with accompanying injuries like sciatic nerve injury, femoral fracture, patellar fracture, and acetabulum and femoral head fracture. [11,12] Only four cases with asymmetric hip dislocation and unilateral acetabular fracture have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In a review of the literature to date, we found totally 58 reported cases of bilateral traumatic hip dislocation. [2,3] Only four cases of asymmetric hip dislocations with unilateral acetabular fracture have been reported to date. [3][4][5][6] A single case of asymmetric hip dislocation with bilateral acetabular fracture has been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When asymmetrical dislocations occur, one posterior and one anterior, it is believed that forces in two opposite directions are needed, making it an extremely rare injury 2, 3…”
mentioning
confidence: 99%
“…These injuries are well-recognized orthopedic emergencies that have steadily increased in incidence for recent decades, presumably because of the increase in high-speed motor vehicle accidents and the failure to wear seat belts, constituting 2% to 5% of all traumatic dislocations. 1,2 Early recognition and a prompt, stable reduction are essential to prevent complications and reduce morbidity. 1,3 The degree of containment of the femur head in the acetabulum usually necessitates a fracture of the acetabular wall when the hip dislocates, and occasionally, there is a concurrent fracture of the head or neck of the femur.…”
mentioning
confidence: 99%